The strange case of Drp1 in autophagy: Jekyll and Hyde?. (15th February 2022) - Chen, Yanfang; Culetto, Emmanuel; Legouis, Renaud
Abstract: There is a debate regarding the function of Drp1, a GTPase involved in mitochondrial fission, during the elimination of mitochondria by autophagy. A number of experiments indicate that Drp1 is needed to eliminate mitochondria during mitophagy, either by reducing the mitochondrial size or by providing a noncanonical mitophagy function. Yet, other convincing experimental results support the conclusion that Drp1 is not necessary. Here, we review the possible functions for Drp1 in mitophagy and autophagy, depending on tissues, organisms and stresses, and discuss these apparent discrepancies. In this regard, it appears that the reduction of mitochondria size is often required for mitophagy but not always in a Drp1‐dependent manner. Finally, we speculate on Drp1‐independent mitochondrial fission mechanism that may take place during mitophagy and on noncanonical roles, which Drp1 may play such as modulating organelle contact sites dynamic during the autophagosome formation. Abstract : Mitochondrial quality control relies on mitophagy. Depending on the organism, cell type and intra‐ or extracellular conditions, the key mitochondrial fission protein Drp1/Dnm1 is either essential or not required during this selective autophagy. This apparent discrepancy highlights the multitasking protein Drp1's hidden sides and the cell resilience mechanisms.